The Influence of MSME Actors’ Income on Increasing Family Welfare in the Kampung Sawah Area - Gulo, Kalvinus; Dina, Nur; Irawan, Pristanto Ria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research examines the relationship between the income of MSMEs and improving the welfare of their families in the Kampung Sawah area, North Jakarta. Consistent and increasing income has the potential to have a positive effect on various aspects of life, including education, health and overall quality of life. However, the relationship between income and community welfare is not always linear and can be influenced by various other aspects, such as individual spending patterns, availability of public services, and local government regulations. This research applies a quantitative descriptive approach, collecting data through surveys and direct dialogue. The sample was selected purposively, involving 73 MSME actors in the Kampung Sawah area, North Jakarta. Data analysis uses a simple linear regression model. Research findings indicate that there is an influence of the income of MSME actors on improving the welfare of their families in the Kampung Sawah area, North Jakarta. It is hoped that this research can become a valuable reference for subsequent studies.